Pulmonary rehabilitation for critically ill elderly patients with COVID-19 in Thailand: Two case reports - Issaragraisin, Thitapa; Champaiboon, Jirapa (Chulalongkorn Medical Journal, 2023)
Many patients exposed to coronavirus disease 2019 (COVID-19) were likely to have complications during their recovery. Critical illness elderly patients with COVID-19 experienced more complications in various systems such as neurological, cardiovascular, mental health, and general deconditioning. There are few publications that mention the impairments of critical illness survivors. Regarding to the limited research evidences we have, this made the physical therapy role challenging. However, we suggest that the physical therapy needs to be fast and more intensive for critical illness in elderly patients with COVID-19. The first case was an old Thai woman presented with severe COVID-19 pneumonia. The other was an old Thai man presented with COVID-19 with complications such as acute respiratory distress syndrome, hyperglycemia, thrombocytopenia, right tension pneumothorax with recurrent pneumothorax, and monoparesis. These two cases presented the experiences and role of physical therapy for critically ill elderly patients with impairments from COVID-19.